2022
DOI: 10.1259/bjr.20211259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast density assessments between synthesized C-View™ & intelligent 2D™ mammography

Abstract: Objectives: To compare breast density assessments between C-View™ and Intelligent 2D™, different generations of synthesized mammography (SM) from Hologic. Methods: In this retrospective study, we identified a subset of females between March 2017 and December 2019 who underwent screening digital breast tomosynthesis (DBT) with C-View followed by DBT with Intelligent 2D. Clinical BI-RADS breast density was obtained along with volumetric breast density measures (including density grade, breast volume, percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, the enhancement may result in false positives due to pseudo-calcifications. 29,35,36 Besides, the C-view image provides poor overall resolution and noise properties compared to the FFDM image. 30,31,40,41 More importantly, large-scale clinical studies reported that more breasts' density is categorized as non-dense than dense when using C-view + DBT compared to using FFDM + DBT, 32,33,37,38 probably due to inherently different visual appearance between the C-view image and FFDM image.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the enhancement may result in false positives due to pseudo-calcifications. 29,35,36 Besides, the C-view image provides poor overall resolution and noise properties compared to the FFDM image. 30,31,40,41 More importantly, large-scale clinical studies reported that more breasts' density is categorized as non-dense than dense when using C-view + DBT compared to using FFDM + DBT, 32,33,37,38 probably due to inherently different visual appearance between the C-view image and FFDM image.…”
Section: Introductionmentioning
confidence: 99%
“…Intelligent 2D was newly developed by Hologic to further improve the performance of C‐view. However, the enhancement may result in false positives due to pseudo‐calcifications 29,35,36 . Besides, the C‐view image provides poor overall resolution and noise properties compared to the FFDM image 30,31,40,41 .…”
Section: Introductionmentioning
confidence: 99%